Haunted destiny - Graham, Heather (Graham, Heather. Krewe of hunters., 2016)
A historic cruise ship, a haunted ship, the Celtic American Line's Destiny sets sail from the Port of New Orleans-with a killer on board. He's known as the Archangel because of the way he displays his victims in churches. And the way he places a different saint's medallion on each one. No one knows exactly who he is or why he's doing this. Jackson Crow, head of the FBI's Krewe of Hunters, a special unit of paranormal investigators,is assigned to the case, along with local agent Jude McCoy. Then Alexi Cromwell, who works in the ship's piano bar, is drawn into the situation when a victim's ghost appears to her and to Jude. A victim who knows only that the man who killed him and his fiancée had boarded the Destiny. Jackson Crow, head of the FBI's Krewe of Hunters, a special unit of paranormal investigators is assigned to the case, along with local agent Jude McCoy. Then Alexi Cromwell, who works in the ship's piano bar, is drawn into the situation when a victim's ghost appears to her and to Jude. A victim who knows only that the man who killed him and his fiancée had boarded the Destiny. There are many suspects, but one by one they're ruled out. Or are they? In the end Jude and Alexi have to rely on each other to catch the killer and to escape his evil plans for her